(untitled) (Research, Society and Development, 2022)
This systematic review aimed to investigate the literature regarding the occurrence and applications of microalgae consortia, in order to search for articles in international journals indexed in the Scopus database. The Systematic Literature Review (SLR) was used to map variables in the literature, such as the most cited publications, evolution of publications, and most relevant journals. The search extracted 278 articles by June 2020. The publications were reduced to 224 articles that comprised the two types of consortium proposed for investigation: 92 articles from the Microalga-Microalga (MM) consortium and 132 articles from the Microalga-Bacteria (MB) consortium. Articles covering consortia in the treatment of effluents were also investigated, which constituted 116 publications in the sample. The survey results show that studies referring to consortium of microalgae have gained prominence in recent years. The performance of consortia in the treatment of effluents and the processing of microalgal biomass in the quantification of bioactives of interest was highlighted as a recurrent theme in the literature. Given the possible applications, the literature reports the use of biomass from the consortium of microalgae generated during the effluent treatment process for its potential in the production of biofuels. On the other hand, implementation of expansive cultivation systems and other alternatives for the application of biomass are still poorly addressed in the literature and are considered research gaps.